Mandibular Distraction Osteogenesis for the Treatment of Neonatal Tongue-Based Airway Obstruction. Issue 3 (May 2015) - Goldstein, Jesse A.; Chung, Cyndi; Paliga, J. Thomas; Cielo, Christopher; Marcus, Carole L.; Lioy, Janet; Bartlett, Scott P.; Taylor, Jesse A.
<x xml:space="preserve">Abstract</x> Abstract Early postnatal tracheostomy for airway compromise is associated with high morbidity and cost. In certain patients with tongue-base airway obstruction (TBAO), mandibular distraction osteogenesis may be preferred. We present a comprehensive analysis of surgical, airway, and cephalometric outcomes in a large series of neonatal patients with TBAO. A retrospective review was performed of patients with laryngoscopically proven TBAO who underwent mandibular distraction osteogenesis before 1 year of age at our institution. Demographic, operative, postoperative, polysomnographic, and radiographic data were analyzed with the appropriate statistical test. Between 2010 and 2013, 28 patients younger than 1 year underwent mandibular distraction for TBAO. Distraction was performed for documented TBAO and failure to thrive at an average age of 58 days (range, 11–312) days with distractor removal after an average of 90 days. Preoperative polysomnograms were obtained on 20 patients with an average apnea-hypopnea index of 39.3 ± 22.0/h; the apnea-hypopnea index on postoperative polysomnograms obtained after distraction completion was significantly reduced in all 14 patients in whom it was measured (mean, 3.0 ± 1.5/h; P < 0.0001). Twenty patients transitioned to oral feeding, and cephalometric and airway diameters were improved (P < 0.0001). Distraction was successful in all but 4 patients including all patients with GILLS scores of 2 or less and 66% of patients with GILLS scores of 3 or greater. Neonatal mandibular distraction is a powerful tool to treat critical obstructive apnea in patients with TBAO. Appropriate patient selection remains a challenge; however, mandibular distraction represents a compelling treatment modality.